Ethylene enhances resistance to cucumber green mottle mosaic virus via the ClWRKY70-ClACO5 module in watermelon plants - Liu, Mei; Kang, Baoshan; Wu, Huijie; Peng, Bin; Liu, Liming; Hong, Ni; Gu, Qinsheng (Frontiers in Plant Science, 2024)
Ethylene (ET) is involved in plant responses to viral infection. However, its molecular mechanisms and regulatory network remain largely unknown. Here, we report that cucumber green mottle mosaic virus (CGMMV) triggers ET production by inducing the expression of ClACO5, a key gene of the ET biosynthesis pathway, in watermelon (Citrullus lanatus). The knock-down of ClACO5 expression through virus-induced gene silencing in watermelon and overexpressing ClACO5 in transgenic Nicotiana benthamiana indicated that ClACO5 positively regulates CGMMV resistance and ET biosynthesis. The salicylic acid-responsive transcription factor gene ClWRKY70 shares a similar expression pattern with ClACO5. We demonstrate that ClWRKY70 directly binds to the W-box cis-element in the ClACO5 promoter and enhances its transcription. In addition, ClWRKY70 enhances plant responses to CGMMV infection by regulating ClACO5 expression in watermelon. Our results demonstrate that the ClWRKY70-ClACO5 module positively regulates resistance to CGMMV infection in watermelon, shedding new light on the molecular basis of ET accumulation in watermelon in response to CGMMV infection.